APPLICATION OF RECURRENT ANALYSIS FOR CYCLIC PROCESSES IN DEMAND-DRIVEN ELECTRICITY GENERATION - YUSKEVYCH, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The increasing demand for flexible and dynamic power systems drives the search for new modeling and forecasting methods. Recurrent analysis, which has gained wide recognition in natural language processing and machine learning, has the potential to become a promising tool for research and optimization of cyclic processes in electricity generation. This paper explores the potential applications of recurrent analysis for addressing various energy-related tasks including electricity demand forecasting, dispatch optimization, power plant scheduling, and consumption data analysis.The paper discusses the advantages of recurrent analysis, such as flexibility, learning ability, and high accuracy, as well as the challenges associated with large data volumes, computational resources, and result interpretation. It emphasizes the prospects of recurrent analysis for developing more efficient, reliable, and sustainable power systems.The article also explores the integration of recurrence analysis with other data-driven techniques such as machine learning and statistical modeling. This integration enhances the predictive capabilities of recurrence analysis, allowing for more accurate and reliable forecasts of energy production and demand cycles. The synergy between recurrence analysis and machine learning algorithms can lead to the development of advanced control systems that dynamically adjust to changing conditions in real-time, thus ensuring a more stable and efficient power supply.In conclusion, the article posits that recurrence analysis holds significant potential for enhancing the understanding and management of cyclic processes in power generation. By providing detailed insights into the temporal dynamics of energy production systems, recurrence analysis can contribute to more efficient and reliable power generation, ultimately supporting the transition to sustainable energy systems. The adoption of recurrence analysis in the energy sector represents a step forward in leveraging advanced mathematical techniques to address the complexities of modern power generation.
Keywords: Recurrent analysis; forecasting; optimization; dispatch control; scheduling; power systems; demand-driven electricity